Higgs factories: Higgsstrahlung versus W fusion - Lafaye, Rémi; Plehn, Tilman (Physical review, 2017)
Higgs factories will be able to measure Higgs properties, and in particular Higgs couplings with high precision. In a follow-up to an earlier analysis we study the impact of the Higgsstrahlung and vector boson fusion processes on the precision of the couplings determination. Provided theoretical uncertainties can be controlled, future Higgs factories will be able to measure Higgs couplings at the subpercent level. In spite of their different strengths, base-line circular and linear designs can expect a surprisingly similar performance.